Evaluation of mandibular motion in adolescents with skeletal class II division 1 malocclusion during mandibular advancement using clear functional aligners: a prospective study - Qiuyue Wu; Yueying Zhang; Hua Xiao; Jiajing Zheng; Tianlu Jiang; Yusen Du; Meng Cao; Feifei Li (BMC, 2024)
Abstract Background This study aimed to evaluate the characteristics of mandibular protrusive condylar trajectory in adolescents with skeletal Class II Division 1 malocclusion and the changes of condylar trajectory during mandibular advancement (MA) treatment using clear functional aligners. Methods This prospective study consisted of a cross-sectional study and a longitudinal study. In cross-sectional study, sixty-one adolescents were divided into two groups: Class I (n = 30) and Class II Division 1 (n = 31). The condylar trajectory was measured and compared using the Mann-Whitney U test. The longitudinal study was the MA treatment group using clear functional aligner and consisted of 16 participants from Class II Division 1group. The condylar trajectory was collected at three-time points: pre-treatment (T1), during MA treatment at approximately 3 months (T2, 105.6 days average), and at the end of MA treatment (T3, 237.6 days average). The changes at T1, T2, and T3, as well as the symmetry between the left and right condyles across all groups, were examined using the Wilcoxon paired test. Results A greater increase in the anteroposterior displacement and space displacement during protrusive movements was observed in the Class II Division 1 group compared with that in the Class I group, with a large difference being observed in the left and right condylar movements. The condylar anteroposterior displacement and space displacement decreased significantly at T2 and increased significantly at T3; however, no significant difference was observed between T1 and T3. A significant difference was observed between the condylar movement on the left and right sides at T1; however, no significant difference was observed at T2 and T3. Conclusions Adolescents with Class II Division 1 malocclusion had higher protrusive capacity than those with Class I. Moreover, their left and right condylar motion was more asymmetric. The range of condyle motion decreased first and then increased during MA therapy, and the left and right condyle movement became more symmetrical, which may be the adaptive response of neuromuscular function to the changes in jaw position.